Menuju Jurnal Merdeka: Pembentuk Hati Nurani Seorang Intelektual Agar Tidak Tunduk Pada Mesin ChatGPT - Manginsela, Elsje Pauline (AGRI-SOSIOEKONOMI, 2023)
In the future, will the human intelligence be replaced by the ChatGPT engines and its derivatives? Many people think so. However actually human intelligence cannot be replaced by machines. ChatGPT was created by a handful of super-intelligent humans backed by a handful of super-rich investors. Therefore actually the intelligence of 99.99 percent of humans on earth is subdued by 0.01 percent of super intelligent and super rich people who want to rule the earth. It is in this case that the intellectuals should prepare themselves so as not to be easily subdued. Merdeka Campus – Merdeka Learning has been implemented in recent years. If the campus is already independent, scientific journals should also be independent. Even though the journal represents a particular scientific specialization, it is necessary to also present other interdisciplinary scientific articles in it. The rigidity of one field of knowledge leads an intellectual to egoism and empty arrogance. Meanwhile, interdisciplinary knowledge brings an intellectual to humble and humane insight. The AGRI-SOSIOEKONOMI Journal wants to appear to defend humanity, not defend monodisciplinary scientific arrogance which has been and will die defeated by artificial intelligence and algorithms. Hopefully this idea will bring dialogue between experts, because that's how academic culture comes alive.